(untitled) - Sreyleap, Kong (Can Tho, 2017)
Biochar could act as a soil conditioner enhancing growth of Chinese cabbages and other vegetables. Effect of biochar is greater when applied together with biodigester effluent. Protein content of Taro and other vegetables is increased when biochar and biodigester effluent applied.
Keywords: Animal feeding,Thức ăn gia súc